Adsorption efficiency of date palm based activated carbon-alginate membrane for methylene blue. (September 2022) - Durrani, Wishal Zia; Nasrullah, Asma; Khan, Amir Sada; Fagieh, Taghreed M.; Bakhsh, Esraa M.; Akhtar, Kalsoom; Khan, Sher Bahadar; Din, Israf Ud; Khan, Muhammad Azam; Bokhari, Awais
Abstract: In the current study, activated carbon (AC) was prepared from date palm using single step activation using boric acid as an activating agent. The synthesized AC was incorporated with alginate (AC-alginate (AC-alg)) to prepare membrane for adsorption of methylene blue (MB) in batch adsorption study. The prepared membrane was characterized using different types of analytical techniques such as FTIR, SEM, and TGA analysis. Adsorption of methylene blue dye from aqueous solution was carried out using AC-alg membrane in batch investigation. Various experimental parameters effecting the adsorption of MB on membrane such as initial pH of dye solution, contact time, concentration of dye solution and temperature were optimized to get maximum adsorption efficiency. Kinetics, isotherm and thermodynamics study was performed for dye adsorption. Pseudo-second order kinetic model and Langmuir adsorption isotherm were well fitted to the experimental data. The maximum adsorption capacity for MB adsorption was 666 mg/g found by Langmuir adsorption isotherm. Thermodynamic study revealed that the adsorption of MB on AC-alg membrane is spontaneous and an exothermic process. The experimental result confirmed that AC-alg membrane is a suitable and easily recoverable adsorbent to be used for efficient removal of MB and MB like other dyes. Graphical abstract: Image 1 Highlights: Activated carbon (AC) was synthesized from date palm using H3 BO4 as an activating agent. AC-alginate composite membrane was synthesized for MB adsorption in batch system. MB adsorption on the synthesized membrane following pseudo-second order kinetic and Langmuir isotherm model. Thermodynamic parameters revealed that the adsorption of MB on the membrane is endothermic and spontaneous in nature.